Estimation of the Public Transport Operating Performance: Example of a Selected City Bus Route - Smieszek, Miroslaw; Kostian, Nataliia; Mateichyk, Vasyl; Mosciszewski, Jakub; Tarandushka, Liudmyla (Communications - Scientific Letters of the University of Zilina, 2023)
The efficiency of the public transport use is a complex indicator formed from a set of partial assessments of its economic, technical and environmental efficiency. Special attention must be paid to the evaluation of efficiency based on energy consumption, taking into account transport work on the city route. The article is devoted to study of the operation performance of a diesel city bus on the selected city route and determines its energy efficiency by specific fuel consumption per unit of transport work. Based on statistical data, the distribution patterns of the speed and acceleration of the bus on the studied route were determined. The analytical dependence of the specific fuel consumption on the average daily passenger flow capacity on the route is obtained and its adequacy is confirmed. Using the dependence obtained, the fuel consumption of the bus was estimated in individual hauls and a certain section of the route.
Keywords: urban public transport; city bus route; operating performance; specific fuel consumption; statistical analysis